Socio-Economic Relationship, Mother's Occupational Status and History of Infectious Diseases in Toddlers Age 12-36 Months - Dewi Andang Prastika; Elisa Ulfiana; Hanifa Andisetyana Putri; Umiyati Umiyati; Aprilia Setiowati (Journal of Midwifery Science: Basic and Applied Research, 2023)
Based on 2018 basic health research data, the stunting rate in Indonesia reaches 30.8 percent, the target of the World Health Organization (WHO) is that the stunting rate should not be more than 20%. In Kapencar village the number of stunting toddlers is still high, from 30.14%, stunting can be caused by low income, maternal employment status and a history of infectious diseases.The purpose of this study was to determine the relationship between socioeconomic status, maternal employment status and history of infectious disease with the incidence of stunting in toddlers aged 12-36 months.This research was conducted in the village of Kapencar. This study uses an analytical survey with a case control design. The population in this study were mothers who had stunted toddlers in the village of Kapencar in the area of the Kertek 2 Health Center. The sampling technique was simple random sampling. The independent variables in this study were socioeconomic status, maternal employment status and history of infectious disease. The dependent variable in this study is stunting.The results showed that there was a significant relationship between the mother's work status (p=0.004; OR=6.120), history of diarrheal disease (p=0.001; OR=9,667), history of respiratory disease (p=0.004; OR=6,600) and the incidence of stunting in toddlers aged 12-36 months. There was no relationship between economic status (p = 0.315; OR = 1.889) with the incidence of stunting.The results of this study are expected for families, especially mothers, to pay more attention to the health status of their toddlers, because with good monitoring attention can provide good care as well.